Pharmacophore Based Drug Designing of COL7A1; The Causative Gene of Dystrophic Epidermolysis Bullosa - Yasra Fatima; Muhammad Aqib Shabbir; Noor-ul-Ain; Syeda Izma Makhdoom; Hamza Saleem-ur-Rehman; Muhammad Waseem; Khizra Jabeen; Syeda Umme Laila; Amna Shahid; Muhammad Naveed (BioScientific Review, 2021)
Epidermolysis Bullosa (EB) is a rare genetic disorder that causes skin fragility, trauma induced dissociation of the skin and painful wound growth. More than 20 types of genes are involved in causing EB as it is a polygenic disease and each gene is involved in causing a different subtype of EB. Dystrophic Epidermolysis Bullosa (DEB) is a subtype of EB caused by mutations in the COL7A1 (Collagen Type VII Alpha 1 Chain) gene and it affects people from all racial backgrounds. No drug is available for the treatment of DEB in the market. So, it is the need of the hour to come up with a potential inhibitor that may inhibit the faulty protein of COL7A1 gene. Different exons of COL7A1 were analyzed and exons 70-75 were selected. These exons are important from a mutational point of view. The mutations in them were identified and verified using various In silico tools. The 3D structure of the protein was retrieved using specific exons (which were edited) and mutations were introduced in it. Moreover, the protein was further checked to analyze its stability, toxicity and solubility. The inhibitors of COL7A1 were formed using CAAD techniques (pharmacophore modeling) and the best inhibitor of COL7A1 was further checked to determine its drug-likeness, solubility, toxicity, and various physiochemical properties. The constructed inhibitor was found to have the best docking results and good ADMET properties. The developed inhibitor construct showed promising results In silico and it is also expected to show good results if it would be tested In vitro and In vivo. Thus, it would be a breakthrough to treat DEB using this inhibitor, if this inhibitor is constructed and further tested In vitro.Keywords: Epidermolysis Bullosa (EB), COL7A1, inhibitors, pharmacophore, skin disordersCopy right (c) The Authors